Patient-specific implants in orbital reconstruction. Issue 4 (August 2022) - Hajibandeh, Jeffrey; Lee, Cameron
Abstract : Purpose of review: Advances in the use of patient-specific implants (PSIs) and virtual surgical planning (VSP) for reconstruction of primary and secondary traumatic orbital defects are explored. Recent findings: PSIs and VSP are emerging technologies that promise to make complex orbital reconstructions safer and more predictable for patients. Recent studies highlight principles of implant design, the novel use of multiunit implant constructs, and utility of intraoperative imaging adjuncts to achieve favorable outcomes. Summary: This article summarizes recent developments in PSIs for orbital reconstruction. A complete workflow including presurgical planning, execution in the operating room, postoperative analysis, and avoidance of common pitfalls and implant design errors are reviewed.